New Approach for Determination of Ciprofloxacin by Quenched Fluorescence of Analytically Interested Species Using Continuous Flow Injection Laser Diode Fluorimeter Analyser - A. Shakir, Issam M.; Hassan , Raed F. (Iraqi Journal of Science, 2022)
The objective of this study was to establish an accurate, precise, sensitive, simple, fast and reliable method for the determination of ciprofloxacin hydrochloride in pure or in pharmaceutical dosage forms using Homemade instrument fluorimeter continuous flow injection analyser with solid state laser (405 nm) as a source. The method is based upon the fluorescence fluorescein sodium salt and its quenching by ciprofloxacin hydrochloride in aqueous medium. The solutions of standard and the sample were prepared in distilled water. The calibration graph was linear in the concentration range of using (10 - 100) mMol.L-1 ciprofloxacin hydrochloride (r= 0.9891) with relative standard deviation (RSD%) for 3 mMol.L-1 ciprofloxacin HCl solution is lower than 2%(n=6). A comparison was made between the newly developed method of analysis with the quoted value using the standard addition method and no significant difference between the new developed method and the quoted value by the manufacturers companies. This indicates clearly that the new method can be successfully used for the assay of the cited day.